Mobile banking services quality and its impact on customer satisfaction of Indonesian Islamic banks - Bayu Arie Fianto; Charissa Kezia Rahmawati; Indri Supriani (Jurnal Ekonomi dan Keuangan Islam, 2021)
Purpose – This study investigates the influential factors of mobile banking service quality dimension (enjoyment, security, ease, design, and application system) of Indonesian Islamic banks toward customer satisfaction.